FDI, Income, and Environmental Pollution in Indonesia - Bachri, Ahmad Alim; Normelani, Ellyn (International Journal of Energy Economics and Policy, 2020)
The research aimed to evaluate the association of disposable income and environmental pollution on the investments measured using FDI (Foreign Direct Investment). The research was specific to the Indonesian economy. The research was secondary quantitative and the data was accumulated from World Bank. The time frame considered for this study ranged from 1960 to 2018. For statistical analysis, descriptive statistics, stationarity testing, ARDL assessment and Granger Causality have been used. The results unveiled that both disposable income and environmental pollution are found to have significant effect on the FDI of Indonesia. Therefore, both the proposed hypotheses have been accepted. The research is limited to Indonesia and no other country has been evaluated. Therefore, in future more countries can be considered for comparative analysis. In furtherance, more factors can be considered in future that affect Indonesian FDI. Keywords: Disposable income, environmental pollution, FDI, Indonesia JEL Classifications: D00, Q50, E22 DOI: https://doi.org/10.32479/ijeep.10537